A systematic study on dispersion stability of carbon nanotube-modified epoxy resins. (January 2015) - Yourdkhani, Mostafa; Hubert, Pascal
Abstract: It is well accepted that the state of dispersion of carbon nanotubes (CNTs) considerably influences the performance of epoxy nanocomposites. Previous studies suggest that CNTs might reagglomerate during the processing of epoxy nanocomposites. Shear forces, resin viscosity, thermal excitation, curing reaction, and CNTs concentration are among the main factors suggested to influence the dispersion stability. The present work focuses on understanding the important role of each parameter on the dispersion stability and explaining the mechanisms by which the dispersion evolves during processing. In this regard, an in-situ dispersion monitoring technique was utilized to acquire dispersion micrographs from the sample of interest during a given heating profile. The results were supported by the rheological and contact angle measurements. It was found out that the increased mobility of CNTs in conjunction with the ineffective interfacial interaction between the nanotubes and resin was the main reason for the degradation of dispersion during the curing process.